Can serum biochemical markers be used to establish a relationship between idiopathic polyhydramnios and antenatal aneuploidy? - Ozgur Sahin; H. Egemen Tolunay; Tufan Arslanca; S. Banu Arslanca (IMR Press, 2021)
Background: Polyhydramnios is a common cause of adverse pregnancy outcomes. The prediction of polyhydramnios in early pregnancy may lead to improved treatments and will diminish these adverse outcomes. Objective: This study aims to investigate the role of biochemical markers in antenatal screening tests to predict idiopathic polyhydramnios. Methods: Patient records were retrospectively evaluated in this case-control group study. Pregnant women (160 in total) were included in the study (this included 47 pregnant women diagnosed with idiopathic polyhydramnios and 113 healthy pregnant women as a control group). Results: Alpha-fetoprotein, unconjugated estriol, and total beta-human chorionic gonadotropin values were similar in both groups (p = 0.296, p = 0.573, p = 0.284). There was no significant difference between the group diagnosed with idiopathic polyhydramnios and the control group when the first-trimester screening test parameter, pregnancy-associated plasma protein-A, was examined (p = 0.102). Conclusion: Biochemical markers examined in prenatal screening tests in the first and second trimesters were insufficient to predict idiopathic Polyhydramnios. The reasons for this are that our study was retrospective, and the patient population was low. We believe that a prospective study with a larger population of patients should be conducted for more meaningful results.